MATH GAMES DOMINO EFFECT ON THE RESULTS OF THE LEARNING MATH FRACTIONS IN CLASS IV SD NEGERI 1 KALIKABONG - Muryaningsih, Sri; Irianto, Sony (Dinamika, 2015)
Abstract. The purpose of this study was to determine: 1) the influence of mathematical domino game against cognitive aspects of mathematics learning outcomes, 2) the influence of mathematical domino game against affective aspects of mathematics learning outcomes 3) the influence of mathematical domino game against psychomotor aspects of mathematics learning outcomes. The research method using experimental research methods to design randomized control group pretest-posttest design. The samples in this study using cluster random sampling. The population in this study is the fourth grade students of SD Negeri 1 and 2 Kalikabong second semester of academic year 2014 / 2015. The experimental classes will be treated mathematics with math domino game material fractions, while grade control using conventional learning. Instruments cognitive aspects of learning outcomes research using test descriptions, research instruments affective aspects of learning outcomes using a questionnaire, and research instruments psychomotor aspects of learning outcomes using performance assessment sheet. Analysis of survey data using statistical analysis independent sample t test with SPSS program. The results showed: 1) a game of dominoes mathematical better effect on the results of the cognitive aspects of learning mathematics, 2) math domino game better effect on the results of the affective aspects of learning mathematics 3) math domino game better effect on psychomotor aspects of mathematics learning outcomes.Keywords: domino mathematical, cognitive, affective, psychomotor Abstrak. Tujuan dari penelitian ini adalah untuk mengetahui: 1) pengaruh permainan domino matematika terhadap hasil belajar matematika aspek kognitif, 2) pengaruh permainan domino matematika terhadap hasil belajar matematika aspek afektif 3) pengaruh permainan domino matematika terhadap hasil belajar matematika aspek psikomotor. Metode penelitian menggunakan metode penelitian eksperimen dengan desain Randomized Control Group Pretest-Postest Design. Pengambilan sampel dalam penelitian ini menggunakan Cluster Random Sampling. Adapun populasi dalam penelitian ini adalah siswa kelas IV SD Negeri 1 dan 2 Kalikabong semester genap tahun pelajaran 2014/ 2015. Kelas eksperimen akan diberi perlakuan pembelajaran matematika dengan permainan domino matematika materi pecahan, sedangkan kelas kontrol menggunakan pembelajaran konvensional. Instrumen penelitian hasil belajar aspek kognitif menggunakan tes uraian, instrumen penelitian hasil belajar aspek afektif menggunakan angket, dan instrumen penelitian hasil belajar aspek psikomotor menggunakan lembar penilaian unjuk kerja. Analisis data hasil penelitian menggunakan analisis statistik independent sample t test dengan program SPSS. Hasil penelitian menunjukkan: 1) permainan domino matematika berpengaruh lebih baik terhadap hasil belajar matematika aspek kognitif, 2) permainan domino matematika berpengaruh lebih baik terhadap hasil belajar matematika aspek afektif 3) permainan domino matematika berpengaruh lebih baik terhadap hasil belajar matematika aspek psikomotor.    Kata kunci : domino matematika, kognitif, afektif, psikomotor